2021
DOI: 10.1001/jamanetworkopen.2021.16543
|View full text |Cite
|
Sign up to set email alerts
|

Association Between COVID-19 Exposure and Self-reported Compliance With Public Health Guidelines Among Essential Employees at an Institution of Higher Education in the US

Abstract: IMPORTANCE Detailed analysis of infection rates paired with behavioral and employee-reported risk factors is vital to understanding how transmission of SARS-CoV-2 infection may be exacerbated or mitigated in the workplace. Institutions of higher education are heterogeneous work units that supported continued in-person employment during the COVID-19 pandemic, providing a test site for occupational health evaluation. OBJECTIVE To evaluate the association between self-reported protective behaviors and prevalence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Weak, but positive associations were reported in three studies (Al‐Shammary 2021 ; Jovančević & Milićević 2020 ; Rattay 2021 (Petra et al, 2021) which examined the role of fear on handwashing, supporting the contention that these behaviours may be driven or motivated by the level of COVID‐19 related fear (Table 9 ). Worry or concern about COVID‐19 was also consistently found to be associated with handwashing behaviours in five of the included studies (Al‐Sejari 2021 ; Callaghan 2021 ; Rattay 2021 ; Shook 2020 (Shook Natalie et al, 2020 ); Nelson 2021 (Nelson Tracy et al, 2021 ), but again, the reported effect sizes for these associations were weak (Table 10 ). One of these studies (Nelson 2021 ) did not report any differences based on whether handwashing behaviour were being carried out in or outside of work contexts.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Weak, but positive associations were reported in three studies (Al‐Shammary 2021 ; Jovančević & Milićević 2020 ; Rattay 2021 (Petra et al, 2021) which examined the role of fear on handwashing, supporting the contention that these behaviours may be driven or motivated by the level of COVID‐19 related fear (Table 9 ). Worry or concern about COVID‐19 was also consistently found to be associated with handwashing behaviours in five of the included studies (Al‐Sejari 2021 ; Callaghan 2021 ; Rattay 2021 ; Shook 2020 (Shook Natalie et al, 2020 ); Nelson 2021 (Nelson Tracy et al, 2021 ), but again, the reported effect sizes for these associations were weak (Table 10 ). One of these studies (Nelson 2021 ) did not report any differences based on whether handwashing behaviour were being carried out in or outside of work contexts.…”
Section: Resultsmentioning
confidence: 93%
“…Worry or concern about COVID‐19 was also consistently found to be associated with handwashing behaviours in five of the included studies (Al‐Sejari 2021 ; Callaghan 2021 ; Rattay 2021 ; Shook 2020 (Shook Natalie et al, 2020 ); Nelson 2021 (Nelson Tracy et al, 2021 ), but again, the reported effect sizes for these associations were weak (Table 10 ). One of these studies (Nelson 2021 ) did not report any differences based on whether handwashing behaviour were being carried out in or outside of work contexts.…”
Section: Resultsmentioning
confidence: 93%
“…37 , 38 In addition to vaccinations, wearing face masks, physical distancing, hand hygiene, and compliance with public health guidelines are effective in reducing spread of COVID-19. 39-42…”
Section: Data Elements and Definitionsmentioning
confidence: 99%
“…37,38 In addition to vaccinations, wearing face masks, physical distancing, hand hygiene, and compliance with public health guidelines are effective in reducing spread of COVID-19. [39][40][41][42] Comprehensive and reliable capture of data elements pertinent to therapeutic procedures in patients with COVID-19 is important to monitor and assess quality of care of these patients with the goal to improve their outcomes. These include but are not limited to data elements pertinent to ventilation and circulatory support, percutaneous interventional therapies, and electrophysiological procedures (Appendix 9).…”
Section: Preventive Therapeutic and Supportive Procedures For Covid-19mentioning
confidence: 99%
“…The pandemic has initiated a wealth of research on COVID-19 and working life. Examples are research on occupational risk factors for SARS-CoV-2 infection ( Beale et al , 2022 ; Lan et al , 2020 ; Magnusson et al , 2020 ; Pearce et al , 2021 ; Verbeeck et al , 2021 ), occupational risk factors for COVID-19 disease and mortality ( Mutambudzi et al , 2020 ; Nafilyan et al , 2021 ; Pearce et al , 2021 ; Senia et al , 2022 ), mitigating factors for risks associated with the SARS-CoV-2 virus ( Iavicoli et al , 2021 ; Nelson et al , 2021 ), and long-term effects of COVID-19 infection often named long-COVID ( Pauwels et al , 2021 ; Rayner and Campbell, 2021 ). Mental health issues related to being an essential worker during the COVID-19 pandemic has also been studied as reviewed in Froessl and Abdeen (2021) .…”
Section: Introductionmentioning
confidence: 99%